Massage techniques – traditions and innovations in their application in Bulgaria historical overview (Research Announcements "Heritage BG", 2025)
Massage is one of the oldest manual methods used for recovery and prevention. It helps overcome stress and fatigue, improves sleep, boosts vitality, and reduces the risk of socially significant diseases. When applied in a specific sequence, massage techniques affect both locally and reflexively the underlying organs and systems. Numerous Bulgarian and international studies confirm the positive impact of this method. In Bulgaria, massage holds a leading position in recreational and therapeutic procedures at specialized Wellness & SPA centers and massage studios, which are gaining increasing popularity.
Keywords: massage; wellness education